2002
DOI: 10.1002/aic.690481210
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of five‐step one‐bed sorption‐enhanced reaction process

Abstract: A fi®e-step, one-bed, sorption-enhanced reaction process proposed by Car®ill et al. in 1996

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
58
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 56 publications
5
58
0
Order By: Relevance
“…22,27 The Xu and Froment steam-reforming kinetics were used previously [16][17][18][19][20]22,27,[29][30][31][32] at temperatures as low as 450°C. Previously, our group 39 also showed the same kinetics to be consistent with experimental data generated with a commercial Ni-based catalyst at temperatures as low as 450°C.…”
Section: Resultssupporting
confidence: 40%
See 2 more Smart Citations
“…22,27 The Xu and Froment steam-reforming kinetics were used previously [16][17][18][19][20]22,27,[29][30][31][32] at temperatures as low as 450°C. Previously, our group 39 also showed the same kinetics to be consistent with experimental data generated with a commercial Ni-based catalyst at temperatures as low as 450°C.…”
Section: Resultssupporting
confidence: 40%
“…They include packed-bed catalytic membrane reactors (MRs) [10][11][12][13][14][15] and, more recently, absorptive reactor (AR) processes. [16][17][18][19][20][21][22][23][24][25][26] Their potential advantages over the more conventional reformers have been widely discussed. They include (i) increasing the reactant conversion and product yield, through shifting of the equilibrium toward the products, potentially allowing one to operate under milder operating conditions (e.g., lower temperatures and pressures and reduced steam consumption), and (ii) reducing the downstream purification requirements by in situ separating from the reaction mixture the desired product hydrogen (in the case of MRs) or the undesired product CO 2 (in the case of ARs).…”
Section: Introductionmentioning
confidence: 43%
See 1 more Smart Citation
“…1 (a)) 7) to multiple step schemes such as pressurized _ (reaction) _ evacuation _ regeneration _ partially pressurized ( Fig. 1 (b)) 8) . Many studies have been reported with the single column system, but complex systems using multiple columns have been applied to industrial processes 9) .…”
Section: P Re S S U Re S W I N G R E a C T O R I N I N T E G R A Tmentioning
confidence: 42%
“…Rodrigues and co-workers [46][47][48][49][50] developed a detailed mathematical model of the abovedescribed PSSER process to simulate its performance for producing fuel-cell grade hydrogen. The model simulations were also used to investigate several new operational schemes for improving the performance of the PSSER process (higher conversion and purer H 2 ).…”
Section: Clean Energy Systems and Experiences 98mentioning
confidence: 45%